ANALISIS DAMPAK PERATURAN DAERAH NO. 2 TAHUN 2015 TENTANG LARANGAN BAGI PEDAGANG KAKI LIMA (PKL) UNTUK BERJUALAN DI TAMAN KOTA DAN TEMPAT UMUM SERTA DAMPAKNYA TERHADAP MINAT WISATAWAN LOKAL UNTUK BERKUNJUNG KE LAPANGAN PUPUTAN BADUNG DI DENPASAR - Nyoman Surya Wijaya; I Wayan Eka Sudarmawan; I Gusti Made Sukaarnawa (Jurnal Ilmiah Hospitality Management, 2018)
ABSTRACTPuputan Badung Park is a green open space located in the centre of Denpasar. The presence of street vendors (PKL) in Puputan Badung Park becomes a particular attraction for local tourists visiting or doing their leisure activity. However, the existence of street vendors sometimes becomes dilemma for the city government. This street vendors sometimes cause pros and cons between citizens and officers. To anticipate this situation, Denpasar city government issued a regulation. This research aims to assess and analyze empirically the impact of the Local Regulation â€œPERDAâ€ No. 2 Year 2015 of the sellingâ€™s prohibition for street vendors (PKL) in city park and in public places towards the interest of local tourists visiting Puputan Badung Park. This research is using positivism paradigm with quantitative data analysis. The X variable is the impact of local regulation â€œPERDAâ€ No.2 Year 2015, and the Y variable is the local tourist interest visiting Puputan Badung Park. The result shows the relation between X and Y with a significance level of 0.008. The value of X and Y also shows a low value of 0.265Â Keywords: Local Regulation â€œPERDAâ€ No. 2 Year 2015, Interests, Puputan Badung Park